Management lore continues alive and well in the organizational sciences - Buckley, M.; Baur, J.; Hardy, J.; Johnson, J.; Johnson, Genevieve; MacDougall, A.; Banford, C.; Bagdasarov, Z.; Peterson, D.; Peacock, J. (2015)
Purpose: The purpose of this paper was to identify examples of management lore currently in the organizational sciences. Design/methodology/approach: The authors deliberated and developed a series of examples of management lore in the organizational sciences and surveyed management practitioners concerning their beliefs in the lore hypothesized. Findings: Pervasive beliefs that conflict with academic research exist in management practices. Although many of these ideas are commonly accepted as immutable facts, they may be based upon faulty logic, insufficient understanding of academic research, anecdotal evidence and an overdependence upon common sense. Buckley and Eder (1988) called these as examples of management lore. In this conceptual paper, we identify and discuss 12 examples of management lore that persist in day-to-day management practices. Topics we explore include personality, emotional intelligence, teams, compensation, goals, performance, work ethic, creativity and organizational citizenship behaviors. Originality/value: Anumber of areas in which academic research gainsays what we believe to be an immutable fact.